2013
DOI: 10.3109/2000656x.2013.863777
|View full text |Cite
|
Sign up to set email alerts
|

The effects of resveratrol on flap survival in diabetic rats

Abstract: Resveratrol is an antioxidant agent with multiple positive impacts on the body. It is known to have anti-diabetic, anti-inflammatory, anti-carcinogenic, and neuroprotective effects. The goal of this study is to demonstrate the antioxidant and anti-diabetic effects of resveratrol on flap survival in diabetic rats. Streptozotocin-induced diabetic Sprague-Dawley albino rats were treated with 10 mg/kg resveratrol following a flap surgery. Histological findings regarding polymorphonuclear leukocyte (PMNL) density, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Several studies reported that resveratrol increases the expression of HO-1 in an Nrf-2-dependent manner ( Gao et al, 2018 ; Zhang Y. et al, 2020 ; Lian et al, 2020 ). In line with this finding, the administration of resveratrol elevated the expression of HO-1 and SOD-1 in random pattern flaps of rats, which was associated with a lower apoptosis rate ( Ciloglu et al, 2014 ; Lin J. et al, 2019 ). Moreover, luteolin and ginkgolide B triggered the gene expression of Nrf-2, leading to elevated HO-1 mRNA levels and higher viability of surgical flaps ( Chen G. et al, 2018 ; Lin D. et al, 2019 ).…”
Section: Effects Of Phytochemicals On Surgical Flapsmentioning
confidence: 73%
See 1 more Smart Citation
“…Several studies reported that resveratrol increases the expression of HO-1 in an Nrf-2-dependent manner ( Gao et al, 2018 ; Zhang Y. et al, 2020 ; Lian et al, 2020 ). In line with this finding, the administration of resveratrol elevated the expression of HO-1 and SOD-1 in random pattern flaps of rats, which was associated with a lower apoptosis rate ( Ciloglu et al, 2014 ; Lin J. et al, 2019 ). Moreover, luteolin and ginkgolide B triggered the gene expression of Nrf-2, leading to elevated HO-1 mRNA levels and higher viability of surgical flaps ( Chen G. et al, 2018 ; Lin D. et al, 2019 ).…”
Section: Effects Of Phytochemicals On Surgical Flapsmentioning
confidence: 73%
“…Additional examples of phytochemicals with a high pro-angiogenic activity promoting flap survival are resveratrol ( Ciloglu et al, 2014 ; Lin J. et al, 2019 ), betulinic acid ( Li et al, 2019 ), salvianolic acid B ( Lay et al, 2003 ; Lin J. et al, 2018 ), and hydroxysafflor yellow A ( Zhang C. et al, 2020 ). All of these compounds simultaneously increase the expression of VEGF and matrix metalloproteinases (MMPs).…”
Section: Effects Of Phytochemicals On Surgical Flapsmentioning
confidence: 99%
“…Previous studies [3,4] have confirmed that ischemiaereperfusion (I/R) injury and neutrophil infiltration result in flap necrosis. Various kinds of agents have been tested to prevent skin flap ischemia, such as resveratrol [5], heparin [6], and vascular endothelial growth factor (VEGF) [7]. Xuebijing (XBJ) injection is an intravenous preparation made from five traditional Chinese medicines, namely Chishao (Radix Paeoniae Rubra), Danggui (Radix Angelica Sinensis), Chuanxiong (Rhizoma Chuanxiong), Honghua (Flos Carthami), and Danshen (Radix Salviae Miltiorrhizae) [8].…”
Section: Introductionmentioning
confidence: 99%